2010
DOI: 10.1002/ajmg.a.33700
|View full text |Cite
|
Sign up to set email alerts
|

Elbow deformities in a patient with mandibuloacral dysplasia type A

Abstract: Mandibuloacral dysplasia (MAD) is a rare autosomal recessive disorder characterized by postnatal growth retardation, craniofacial anomalies, mandibular hypoplasia with dental overcrowding, micrognathia and narrow nasal bridge and tip, skeletal anomalies (progressive osteolysis of the clavicles and distal phalanges, delayed closure of the cranial sutures, and joints contractures) and skin changes including mottled hyperpigmentation and atrophy. We and others have already reported lipodystrophy and metabolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is well established that abdominal obesity confers increased risk of metabolic complications, whereas preferential fat accumulation in gluteofemoral region is associated with a lower risk [4] and, accordingly to lessons learned from lipodystrophies, may be even protective [5][6][7]. In addition, there are numerous smaller visceral adipose depots such as epicardial (EAT) and intermuscular adipose tissue [8] that may serve specialized functions related to their neighboring tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that abdominal obesity confers increased risk of metabolic complications, whereas preferential fat accumulation in gluteofemoral region is associated with a lower risk [4] and, accordingly to lessons learned from lipodystrophies, may be even protective [5][6][7]. In addition, there are numerous smaller visceral adipose depots such as epicardial (EAT) and intermuscular adipose tissue [8] that may serve specialized functions related to their neighboring tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results of one of these trials have in fact demonstrated beneficial effects of zoledronate on bone mineral density in patients, although undesired side effects on the cardiovascular system have been also reported [ 110 ]. However, since osteolysis appears to be a generalized feature of all MAD forms [ 111 ], anti-resorptive therapy may be considered an option to prevent or delay irreversible bone deformities [ 112 ].…”
Section: Lamins and Bone Turnovermentioning
confidence: 99%
“…The influence of obesity on T2DM risk is determined not only by the degree of obesity but also by distribution of fat mass. Indeed, whereas abdominal obesity confers an increased risk for T2DM, metabolic syndrome and cardiovascular disease, preferential fat accumulation in gluteo‐femoral region confers a lower risk and, as learned from lipodystrophies, may be even protective . In addition, there are numerous ectopic fat depots that may serve specialized functions related to their neighbouring tissues, playing an emerging local pathophysiological role in obesity complications.…”
Section: The Causal Link Between Obesity and Type 2 Diabetesmentioning
confidence: 99%